Altering One's Body-Perception Through E-Textiles and Haptic Metaphors - Tajadura-Jiménez, Ana; Väljamäe, Aleksander; Kuusk, Kristi (Frontiers in Robotics and AI, 2020)
While e-textiles are a key component in exergame or space suits, the transformative potential of the internal side of garments to create embodied experiences still remains largely unexplored. This paper is the result from an art-science collaborative project that combines recent neuroscience findings, body-centred design principles and 2D vibrotactile array-based fabrics to alter one’s body perception. We describe an iterative design process intertwined with two user studies on the effects on body-perceptions and emotional responses of various vibration patterns within textile that were designed as spatial haptic metaphors. Our results show potential in considering materials (e.g., rocks) as sensations to design for body perceptions (e.g., being heavy, strong) and emotional responses. We discuss these results in terms of sensory effects on body perception and synergetic impact to research on embodiment in virtual environments, human-computer interaction and e-textile design. The work brings a new perspective to the sensorial design of embodied experiences which is based on “material perception” and haptic metaphors, and highlights potential opportunities opened by haptic clothing to change body-perception.